Use of Integrated Optical Clearing and 2-Photon Imaging to Investigate Sex Differences in Neuroimmune Interactions After Peripheral Nerve Injury - Szabo-Pardi, Thomas A.; Syed, Umar M.; Castillo, Zachary W.; Burton, Michael D. (Frontiers in Cell and Developmental Biology, 2021)
Peripheral nerve injury induces a myriad of immune-derived symptoms that negatively impacts pain, depression, and overall quality of life. Neuroimmune differences underlie sexual dimorphisms in various pain states. The innate immune system is a source of these sex differences, which promotes inflammation and pro-nociception through bidirectional signaling with the nervous system. Spatiotemporal interactions between leukocytes and sensory neurons could hold the key to explain ascribed differences between sexes. To date, studies have found it difficult to display these interactions. We are poised to answer important questions regarding the recruitment of peripheral leukocytes to key tissues of the pain system, the dorsal root ganglia (DRG) and sciatic nerve after nerve injury. We optically clear whole DRGs and sciatic nerves and concomitantly use multi-photon microscopy and transgenic reporter lines, to visualize leukocyte dynamics involved in neuropathic pain development following nerve injury. We observed robust sexual dimorphisms in leukocyte recruitment to the lumbar DRGs after nerve injury. We also assessed immune cell size and morphology to understand activation states in the context of nervous tissue inflammation. The altered mechanisms by which the male and female immune systems respond to nerve injury are still topics of further research, however; the continued use of next-generation imaging with advanced whole tissue image analysis remains an important tool in understanding the reciprocal interactions between neuronal and nonneuronal cells.